Associated Factors of Intracranial Hemorrhage in Patients with Nontraumatic Headache who Underwent Anticoagulation Therapy; A retrospective study - Khaled Almansoor, Shaikha; Hussein Alkohlani, Albatoul; Kaiser Abdulwali, Sameeha; Aldahoul, Sarah; Hamdan, Dalia; Desai, Sameer; Alobathani, Danah; Qureshi, Muhammad (Archives of Academic Emergency Medicine, 2026)
Introduction: Although anticoagulation is a well-established risk factor for intracranial hemorrhage (ICH) following trauma, its role in determining the need for neuroimaging in patients with nontraumatic headache is less clear. This study evaluated whether anticoagulation alone justifies brain computed tomography (CT) scan imaging in non-traumatic headache. Methods: We conducted a retrospective cohort study at a tertiary care center in Riyadh, Saudi Arabia, including adults presenting with nontraumatic headache between January 2020 and 2023. Patients who underwent brain CT scan were assessed for hemorrhage and potential associated factors of ICH were explored. Results: Among 909 patients who presented with non-traumatic headache, 162 (17.82%) cases were on anticoagulation therapy, and 20 (2.2%) had ICH on brain CT scan. Anticoagulation use alone was not significantly associated with the risk of ICH following nontraumatic headache (p = 0.068). A history of prior ICH or ischemic stroke emerged as a predictor of ICH, in the overall cohort and among anticoagulated patients (p < 0.001 for all comparisons). No statistically significant associations were observed with antiplatelet use, anticoagulant type, combined anticoagulant–antiplatelet therapy, or neurological deficits. Conclusion: It seems that, in patients presenting with nontraumatic headache, anticoagulation use alone should not dictate the decision to perform brain CT scan. A history of prior ICH or ischemic stroke is a more reliable predictor of ICH risk and should be prioritized in imaging decisions. These findings support a more targeted imaging strategy to minimize unnecessary scans and improve emergency department resource utilization.